Evaluation and Management of Hepatic Encephalopathy: Current Status and Future Directions - Suraweera, Duminda (Gut Liver, 2016)
Hepatic encephalopathy is a spectrum of neurocognitive manifestations often seen in patients with liver injury or rarely in patients with portosystemic shunting without liver injury. It can be divided into minimal (covert) hepatic encephalopathy and overt hepatic encephalopathy, depending on the severity. Patients with hepatic encephalopathy have compromised clinical outcomes, decreased quality of life, and increased healthcare utilization, often resulting in a heavy financial and personal burden on caregivers. The diagnosis remains largely clinical, with the exclusion of possible other causes for the altered mental status. Current treatment strategies include nonabsorbable disaccharides and antibiotics. This review will focus on the diagnosis, management and clinical impact of hepatic encephalopathy.